Validity and reliability of Polar Team Pro GPS units for assessing maximum sprint speed in soccer players - Sagiroglu, I.; Akyildiz, Z.; Yildiz, M.; Clemente, F. M. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2023)
Previous research has reported inconsistencies in the validity and reliability of different brands of global positioning systems (GPS). Therefore, it should be questioned whether GPS units measure the maximum speed measurements validly and reliably. The current study aimed to analyze the validity and reliability of Polar Team Pro GPS units (10 Hz) when used to measure maximum sprint speed. Sixteen amateur soccer players (age: 27.22 ± 4.70 years; height: 177 ± 6.05 cm; body mass: 73.66 ± 5.63 kg) were tested in the 40 m sprint. Two Polar Team Pro GPS units were positioned on each player, while the radar was placed on a 1 m high tripod placed 10 m behind the starting point. The data obtained from the Polar Team Pro GPS units were compared to determine inter-unit reliability. The data obtained from one of the Polar Team Pro GPS units and radar gun (gold standard) were compared to determine validity. Good inter-unit reliability between the Polar Team Pro GPS units was reported for maximum sprint speed, with low coefficients of variation (5%-6%) and low smallest worthwhile changes (0.4 for all systems). Regarding validity, the coefficient of correlation was extremely high for maximum sprint speed (r = 0.938, p < 0.001). Moreover, measurement differences between both systems were statistically insignificant (Mean Bias error = 0.144, R2 = 0.879, MAPE = 1.6%, MAE = 0.688, and RMSE = 0.697). Consequently, good reliability and perfect validity were observed, indicating that the Polar Team Pro GPS unit is suitable for maximum sprint speed measurements.